A5: Detectable Anti‐Infliximab Antibodies in Children Treated with Infliximab for Rheumatic Diseases. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Aeschlimann, Florence A.; Hofer, Kevin; Schneider, Elvira Cannizzaro; Schroeder, Silke; Lauener, Roger; van der Kleij, Desiree; Rispens, Theo; Saurenmann, R.K.
Abstract : Background/Purpose: Infliximab (IFX) is a monoclonal TNF‐alpha inhibiting antibody which is frequently used to treat children with refractory arthritis and uveitis. The most frequent and limiting adverse events are infusion reactions associated with the presence of anti‐drug antibodies. Objectives: To describe the incidence of detectable anti‐IFX antibodies and the correlation with infusion reactions and patient characteristics. Methods: Blood samples were collected before infusion between Aug 2009 and April 2013 every 6 months in all patients treated with IFX at our department. Patients' charts were retrospectively reviewed for IFX infusion reactions. Factors such as IFX dosage, infusion interval, co‐medication and time until first occurrence of an infusion reaction were collected and statistical analysis performed in search for possible correlation. Anti‐IFX antibody testing was performed using a Radio Immuno Assay developed by Sanquin laboratories (www.sanquin.nl ). Results: A total of 288 samples from 64 patients (70% females) were tested. Diagnosis was JIA in 37/64 (58%), JIA with uveitis in 17/64 (27%) and 10/64 (16%) had isolated uveitis. The indication for IFX treatment was arthritis in 38 (59%) patients and uveitis in 25 (39%) patients. In one patient an associated Crohn's disease was the indication for IFX treatment. Anti‐IFX antibodies resulted positive in 53/288 (18%) samples of 15/64 (23%) patients after a mean IFX treatment time of 1065 days (range 42–3498 days). Titers of anti‐IFX antibodies varied between 12–120, 000 AU/ml with a median of 160 AU/ml. Seven patients with positive antibodies (47%) also had ≥1 infusion reaction (median antibody titer 290 AU/ml, range 13–120, 000). The median antibody concentration among patients without infusion reactions was 36 AU/ml (range 12–430). Among the 49 patients without detectable antibodies, 3 (6%) had a history of infusion reactions (p = 0.005 Chi square). In 3/15 (20%) patients the occurrence of anti‐IFX antibodies was associated with a disease flare, two of them experienced simultaneously an infusion reaction. Presence of anti‐IFX antibodies increased with the duration of IFX treatment (p = 0.0002) and was more commonly found in patients with arthritis as the treatment indication p = 0.005), in girls (p = 0.03), in children with a younger age at IFX start (p = 0.02) and was less common in patients who had received systemic steroids at some point during IFX treatment (p = 0.05). A multivariate analysis was performed with all factors positive in the univariate analysis using a stepwise regression model. The age at IFX start was the most significant factor (p = 0.003), followed by arthritis as treatment indication (p = 0.008) and systemic steroid treatment (p = 0.05), while the total duration of IFX therapy (p = 0.07) and gender (p = 0.19) were not significantly associated with anti‐IFX antibodies. Conclusion: In our cohort 15/64 (23%) patients developed detectable anti‐IFX antibodies with infusion reactions occurring in 47% of them. A younger age at start of IFX treatment was associated with the development of antibodies while uveitis as a treatment indication and co‐medication with systemic steroids at some point during IFX therapy were associated with a lower antibody frequency.